Pharmacokinetic and pharmacodynamic similarity between SAR341402 insulin aspart and Japan-approved NovoRapid in healthy Japanese subjects - Masanari Shiramoto (Nature Portfolio, 2021)
Abstract This study compared the pharmacokinetic and glucodynamic profiles of biosimilar SAR341402 insulin aspart to Japan-approved insulin aspart (NovoRapid) in healthy Japanese males. In this single-center, randomized, double-blind, single-dose, two-period, crossover study, subjects received 0.3 U/kg of SAR341402 or NovoRapid before undergoing a 10 h euglycemic clamp procedure. Plasma insulin aspart concentrations and blood glucose levels were measured, and glucose infusion rates (GIRs) were assessed. Primary endpoints were maximum plasma insulin aspart concentration (INS-Cmax), area under the plasma insulin concentration–time curve to the last quantifiable concentration (INS-AUClast), area under the GIR–time curve during the clamp (GIR-AUC0–10 h), and maximum GIR (GIRmax). Forty subjects were randomized with 39 completing both treatment periods. Pharmacokinetic exposure showed a mean ratio between products of 1.00 (90% confidence interval [CI] 0.94–1.05) for INS-Cmax and 1.02 (90% CI 1.00–1.04) for INS-AUClast. Glucodynamic activity showed a mean ratio between products of 1.00 (95% CI 0.93–1.06) for GIR-AUC0–10 h and 1.01 (95% CI 0.95–1.08) for GIRmax. The 90% CIs for pairwise treatment ratios were within the predefined equivalence range of 0.80–1.25. Both treatments were well tolerated. We concluded that similar pharmacokinetic exposure and glucodynamic potency were shown for SAR341402 and NovoRapid in healthy Japanese males.